Primary perforated cancer of ascending colon in diverticulum - Korczewska-Niegierysz, Emilia; Kędra, Bogusław; Grassman, Magdalena; Zaręba, Konrad; Roszkowski, Andrzej (Contemporary Oncology/Współczesna Onkologia, 2009)
Cancer and diverticular disease are very common diseases of large intestine. Never the less the cancer which is situated in diverticulum is rare. There are two kinds of diverticulum- true diverticulum, and pseudo- diverticulum. False- diverticulum- a diverticulum of the intestine that passes through a defect in the muscular wall of the gut and thus does not include a layer of muscle in its wall. True diverticulum- a diverticulum that includes all the layers of the wall from which it protrudes. False diverticula are generally localized in the left side of colon, especially in sigmoid, while true diverticula are congenital, and situated in the right side. Many people develop diverticula that produce no symptoms. Possible complications of diverticulitis include the development of stricture, fistula, or peritonitis. Hardly ever the cancer grows up in diverticulum. In our report we examine the case of a patient who had a primary colon cancer which was situated in true diverticulum of the ascending colon.